Content Vol. 43 No. 2 (2022) - Coordinador Editorial (Revista Mexicana de Ingenieria Biomedica, 2022)
E-book edition of the volume 43, number 2, year 2022, of the Revista Mexicana de Ingeniería Biomédica. In this issue: Hydroxyapatite and Biopolymer Composites with Promising Biomedical Applications Studying the Effect of Temperature on the Tensile Strength of an Intravascular Catheter Using a Degradation Model Comparison of Accuracy of Color Spaces in Cell Features Classification in Images of Leukemia types ALL and MM Retinal Lesion Segmentation Using Transfer Learning with an Encoder-Decoder CNN Secure Exchange of Medical Images Via Extended Visual Cryptography